2015
DOI: 10.1161/strokeaha.115.009961
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute Stroke Protocol Activation in a Children’s Hospital Emergency Department

Abstract: Background and Purpose-Pediatric acute stroke teams are a new phenomenon. We sought to characterize the final diagnoses of children with brain attacks in the emergency department where the pediatric acute stroke protocol was activated and to describe the time to neurological evaluation and neuroimaging. Methods-Clinical and demographic information was obtained from a quality improvement database and medical records for consecutive patients (age, ≤20 years) presenting to a single institution's pediatric emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 14 publications
2
82
0
2
Order By: Relevance
“…The study, conducted from 2011 to 2014 reported 124 stroke alerts in a pediatric emergency room, including 30 children with stroke. 7 MRI, the initial imaging study in 76%, was completed at median 94 minutes from hospital arrival compared to 59 minutes for CT. These data prove the feasibility of rapid MRI as a first imaging test and provide a criterion standard to which all specialized pediatric stroke centers can aspire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study, conducted from 2011 to 2014 reported 124 stroke alerts in a pediatric emergency room, including 30 children with stroke. 7 MRI, the initial imaging study in 76%, was completed at median 94 minutes from hospital arrival compared to 59 minutes for CT. These data prove the feasibility of rapid MRI as a first imaging test and provide a criterion standard to which all specialized pediatric stroke centers can aspire.…”
Section: Discussionmentioning
confidence: 99%
“…Children present age-related challenges to timely diagnosis, including stroke mimics in 30% to 75% and subtle clinical presentations, which necessitates neuroimaging confirmation of stroke before administering treatment. [5][6][7] Seizures in 22% to 25% at pediatric stroke onset (10-fold increase over adults) confound stroke diagnosis, accelerate ischemic injury, and entail urgent consideration of anticonvulsants for neuroprotection. 8,9 Studies to date, however, report intervals of 16 to 25 hours from symptom onset to stroke diagnosis 1,8,[10][11][12][13][14] far beyond 4.5 to 6 hours, the time window recommended for thrombolysis or embolectomy in adults.…”
mentioning
confidence: 99%
“…11 Neuroimaging was required to differentiate strokes from mimics. 10,11 The present study underscores the high frequency of stroke mimics in children, which makes the job of emergency physician evaluators even more difficult. Although the overall specificity of ED physician suspicion of stroke was high, the sensitivity was only moderate to good.…”
mentioning
confidence: 84%
“…In another study of final diagnoses among 124 stroke alerts in a pediatric ED, 76% had stroke mimics. 10 However, in a different tertiary care hospital cohort, only 21% of children evaluated by the stroke team for acute presentations concerning for stroke had mimics. 11 Neuroimaging was required to differentiate strokes from mimics.…”
mentioning
confidence: 96%
See 1 more Smart Citation